Predicting cardiovascular disease in patients with mental illness using machine learning - Martin Bernstorff; Lasse Hansen; Kevin Kris Warnakula Olesen; Andreas Aalkjær Danielsen; Søren Dinesen Østergaard (European Psychiatry)
Abstract